CRANKTRAIN DYNAMICS SIMULATION (Perner's Contacts, 2012)
This paper presents advanced and efficient computational approaches to an analysis of cranktrain dynamics. The approaches are represented by complex computational model of a powertrain (virtual engine) which is a powerful tool for the solution of structural, thermal and fatigue problems. The computational model of dynamics includes flexible parts and hydrodynamic approach for slide bearing solution. Presented virtual engine is assembled as well as numerically solved as a Multi-Body System and it is focused on cranktrain vibrations identification. Virtual engine results are validated by measurements on a compression-ignition in-line four-cylinder engine.
Keywords: cranktrain, dynamics, vibrations, virtual engine